2011
DOI: 10.1073/pnas.1105688108
|View full text |Cite
|
Sign up to set email alerts
|

Role of low-frequency HIV-1 variants in failure of nevirapine-containing antiviral therapy in women previously exposed to single-dose nevirapine

Abstract: In the OCTANE/A5208 study of initial antiretroviral therapy (ART) in women exposed to single-dose nevirapine (sdNVP) ≥6 mo earlier, the primary endpoint (virological failure or death) was significantly more frequent in the NVP-containing treatment arm than in the lopinavir/ritonavir-containing treatment arm. Detection of NVP resistance in plasma virus at study entry by standard population genotype was strongly associated with the primary endpoint in the NVP arm, but two-thirds of endpoints occurred in women wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 19 publications
5
61
0
Order By: Relevance
“…Preexisting dominant NVP mutations were a major risk factor for failure. Subsequent studies also showed that a high risk of treatment failure was also observed in women who had received single-dose NVP and had NVP-resistant HIV-1 variants at low frequency (49,71).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preexisting dominant NVP mutations were a major risk factor for failure. Subsequent studies also showed that a high risk of treatment failure was also observed in women who had received single-dose NVP and had NVP-resistant HIV-1 variants at low frequency (49,71).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there have been few research studies examining the impact of low-frequency drug-resistant HIV-1 variants in treatment-experienced patients due to the current success of cART in HICs; very low failure rates; and, so far, limited availability of clinical tests aimed at quantifying low-frequency HIV-1 variants (24,73). The OCTANE/A5208 study by the AIDS Clinical Trial Group provides our best indication that low-frequency mutations can impact treatment outcomes (49,71,74,75). Women who had previously received a single-dose of NVP to prevent mother-to-child transmission had a 30% rate of treatment failure if randomized to receive an NVP-containing regimen versus a Ͻ10% failure rate with a ritonavir-boosted lopinavir (LPV/r)-containing regimen of FTC plus TDF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV genotyping is routinely performed by Sanger sequencing of plasma HIV RNA; however, this technology is too costly and technically demanding to implement in most low-resource laboratories and clinics. Furthermore, the sensitivity of consensus sequencing is limited for minor variants constituting Ͻ25% of the viral population (7,8), although low-frequency HIV drug resistance mutations, particularly involving resistance to nonnucleoside reverse transcriptase (RT) inhibitors (NNRTIs), have been associated with increased risks of virological failure with first-line ART (9)(10)(11)(12)(13)(14)(15). Therefore, sensitive and affordable assays are needed to monitor HIV drug resistance as part of global HIV treatment programs.…”
mentioning
confidence: 99%
“…Among those with NVP resistance, 73 % in the NVP group compared to only 6 % in the LPV/rt group died or had virologic failure (p = 0.006). Analysis of the OCTANE participants revealed that at the time of starting ART with an NNRTI regimen, those women with either K103N or Y181C at a concentration >1 % of the plasma HIV population by AS-PCR testing were at increased risk of virologic failure or death (HR 2.93, 95 % CI 1.27-6.75) (Boltz et al 2011). This finding supports the assertion that minority variant resistant virus can impact the response to ART and highlights the potential impact of sensitive resistance assays for women who used sdNVP.…”
Section: Effects Of Sdnvp On Efficacy Of Subsequent Nnrti-based Art Imentioning
confidence: 98%